2021
DOI: 10.1136/rmdopen-2020-001324
|View full text |Cite|
|
Sign up to set email alerts
|

Current status of use of high throughput nucleotide sequencing in rheumatology

Abstract: ObjectiveHere, we assess the usage of high throughput sequencing (HTS) in rheumatic research and the availability of public HTS data of rheumatic samples.MethodsWe performed a semiautomated literature review on PubMed, consisting of an R-script and manual curation as well as a manual search on the Sequence Read Archive for public available HTS data.ResultsOf the 699 identified articles, rheumatoid arthritis (n=182 publications, 26%), systemic lupus erythematous (n=161, 23%) and osteoarthritis (n=152, 22%) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…According to the authors, the most studied entities among the rheumatic diseases are rheumatoid arthritis, systemic lupus erythematous and osteoarthritis (OA). Whole exome sequencing (WES) and target panels are estimated to consist about 24% of applications used in high throughput methods used in research in rheumatology [ 72 ]. However, especially WES reveals high diagnostic potential.…”
Section: Panels Whole-genome and -Exome Sequencing In Diagnosticmentioning
confidence: 99%
“…According to the authors, the most studied entities among the rheumatic diseases are rheumatoid arthritis, systemic lupus erythematous and osteoarthritis (OA). Whole exome sequencing (WES) and target panels are estimated to consist about 24% of applications used in high throughput methods used in research in rheumatology [ 72 ]. However, especially WES reveals high diagnostic potential.…”
Section: Panels Whole-genome and -Exome Sequencing In Diagnosticmentioning
confidence: 99%
“…Despite the large number of microarray SLE sequencing studies, most of the data are underutilized, leaving substantial information that has not been mined in-depth. 7 Therefore, in the present study, we conducted an integrated analysis by combining reported gene profile and immunochip data 8 to screen for SLE-related SNPs. This analysis can yield new reliable biomarkers to better understand the pathogenesis of SLE.…”
Section: Introductionmentioning
confidence: 99%